2015
DOI: 10.13005/bbra/1889
|View full text |Cite
|
Sign up to set email alerts
|

“In-silico Prediction of Riboswitches and Design of their Potent Inhibitors for H1N1, H2N2 and H3N2 Strains of Influenza Virus”

Abstract: Almost every age group is at higher risk for serious flu complications. The major problem arising these days regarding the control of influenza disease is the development of resistance among the influenza viruses against the existing anti-viral drugs that are being recommended. Also, these antiviral drugs have a number of side effects. The main objective of the present paper is to explore riboswitches as a novel target for design of drugs for influenza virus in order to address the issues of resistance and sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The generated grid box was then utilized to perform all the docking cycles in the current in silico studies. The grid box was located by considering the ligand as a centre, and also by wrapping each of the macromolecular residues interacting with the ligand to make sure that every possible ligand conformation falls inside the grid box [12,[20][21][22]. The grid box used in the current in silico studies is shown in Figure 2.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated grid box was then utilized to perform all the docking cycles in the current in silico studies. The grid box was located by considering the ligand as a centre, and also by wrapping each of the macromolecular residues interacting with the ligand to make sure that every possible ligand conformation falls inside the grid box [12,[20][21][22]. The grid box used in the current in silico studies is shown in Figure 2.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The parameters used in the current docking protocol were validated using resemblance between the chemical interactions observed in the conformation of the reference ligand docked with the macromolecular target, and the interactions of the bioactive crystallized conformation present in the bioactive crystallized macromolecular complex structure [14,[22][23][24][25].…”
Section: (B) Chemical Resemblancementioning
confidence: 99%
“…[15,16] The complexed antifolate ligand 18G was separated from the macromolecular complex by using software Chimera. [17] The macromolecular target was prepared for molecular docking simulation by addition of polar hydrogens and Gasteiger charge to the amino acid residues with even distribution [12,18,14]. Ligand 18G was prepared for the docking simulation by assigning nonrotatable, rotatable and unrotatable bonds.…”
Section: Molecular Docking Simulationmentioning
confidence: 99%
“…AutoDock is a suite of free open-source software for the computational docking and virtual screening of small molecules to macromolecular receptors. The suite presently includes several complementary tools, in which have used AutoDock [16,[24][25][26] (a computational docking program based on an empirical free-energy force field and rapid Lamarckian genetic algorithm search method [27] ) and Raccoon (an interactive graphical tool for virtual screening and analysis [28] ) tool. In the discussed study, four protein from Mtb as a receptor was used.…”
Section: Molecular Dockingmentioning
confidence: 99%